CHINESE ETHNIC STRATEGIES IN MAINTAINING BAHASA INDONESIA IN THE COMMUNITY (STRATEGI ETNIS TIONGHOA DALAM MEMPERTAHANKAN BAHASA INDONESIA DI KOMUNITASNYA) - Afrinda, Putri Dian; Rahmat, Wahyudi (Jurnal Gramatika, 2019)
The problem in this study is how the strategies carried out by ethnic Chinese in maintaining Indonesian in their community. In the daily life of the ethnic Chinese they joke with their communities, they still use Indonesian. The Indonesian language used is of course Indonesian which has been mixed with code. The purpose of this paper is to find out the factors that influence the retention of Indonesian in the Chinese community. Data was collected by direct observation, and interviews with informants who were ethnic Chinese. The speakers in this paper are ethnic Chinese from various circles, both parents, teenagers and children. Respondents were selected based on criteria as native or ethnic Chinese who reside in Padang, West Sumatra. The results of the study indicate that one of the strategies in maintaining Indonesian language for the Chinese ethnics in the community is found in several forms of Indonesian language defense in the form of code mixing. The form of code mix that is found is the fragments of words, and Chinese phrases in Indonesian sentences. Fragment categories of words and phrases found are verbs, objects, properties, information and numerals. This is one of their strategies in maintaining Indonesian.